The effects done by an electromagnetic pulse generator based on Marx Generator towards nearby conductors and electronic components. / Muhammad Adib Akram Mohdami Norashid - Mohdami Norashid, Muhammad Adib Akram (2013)
An EMP Generator device is designed by combining a Cockcroft Walton Voltage Multiplier towards a Marx Generator. The spark is directed towards a 1600 rotation coil to direct the EMP in linear formation. Over voltages exceeding 1kv is detected along with over currents exceeding 20 ampere by measuring the currents induced in the middle of the coil. The second identical coil is placed beside primary coil to receive maximum induction and measuring voltage and current of the second coil yield the same result. Increasing the distance between coils decreases the occurring of over currents almost linearly. The pulsing current is directed into a 7402 IC and the functions failed after checked by IC checker. The performance of EMP Generator device is discussed if used in a large scale in military weaponry.